Impact of establishment methods, variety and crop spacing on rice (Oryza sativa) productivity using drip irrigation - KANNAN, S VALLAL; RAVIKUMAR, V (The Indian Journal of Agricultural Sciences, 2025)
An experiment was conducted during during winter (rabi) season of 2018–2021 at Agricultural Engineering College and Research Institute, Kumulur, Tamil Nadu to develop a compendium technology for a drip irrigation system by combining suitable establishment methods along with variety and spacing to achieve productivity enhancement in rice (Oryza sativa L.) productivity and efficiency enhancement in a drip irrigation system. The experiment was laid out in a split-split plot design (SSPD) replicated thrice. Two methods of the establishment of direct seeding in a raised bed and transplanting in a flatbed was the main plot treatment; three medium duration of ADT 54, TKM 13 and CR 1009 sub-1variety was the sub plot treatment; and three different spacing of 20 cm × 10 cm, 20 cm × 20 cm, and 25 cm × 25 cm was the sub-sub plot treatment. Results revealed that direct seeded rice in a raised bed by using TKM 13 at 20 cm × 20 cm combined with recommended agronomic practices for medium duration variety is the best compendium technology for achieving the higher productive tillers of 375/m2, number of filled grains of 45,375/m2, grain yield of 6,080 kg/ha, net return of ₹64,059/ha, Benefit: Cost ratio (B:C) of 2.37 in addition to the water use efficiency of 6.61 kg/ha-mm and water productivity of ₹10.57/m3 in drip method of irrigation system in rice cultivation.